The Relationship Between Selected Sensorimotor Abilities and Shooting Accuracy Among Soccer Players - Mahmood Munshid Murshed (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
In this research, it was intended to find out the relationships between selected sensorimotor abilities and shooting accuracy of soccer players. The use of descriptive correlational design was appropriate for this study as a result of it being related to the study's nature and purpose. The study's population was composed of 24 soccer players who belonged to the Al-Shirqat Sports Club team. A purposive sampling technique was applied to select a sample size of 10 players, which constituted 41.66% of the population. The objectives of the study were accomplished by conducting several sensorimotor abilities' tests; namely, foot lateral-distance perception, sensorimotor perception of the foot in the vertical plane, ball-throw perception, and shooting accuracy test. Statistical analysis was done using arithmetic mean, standard deviation, Pearson's simple correlation coefficient, and percentage. The mean score for shooting accuracy was 6.9 (SD = 2.46), while the foot lateral-distance perception, vertical foot position sense, and ball-throw perception tests yielded mean scores of 10.0 cm (SD = 3.60), 13.7 cm (SD = 4.22), and 9.3 cm (SD = 2.46), respectively. Significant correlations were found between shooting accuracy and selected sensorimotor abilities. This means that there is a contribution of selected sensorimotor abilities in improving shooting accuracy of soccer players. According to these findings, the researcher suggests incorporating sensorimotor ability training practices within the training programs of soccer players along with conducting regular testing.